PERANCANGAN SISTEM INVENTORY RUANG KELAS DENGAN PENDEKATAN METODE QUALITY CONTROL STATISTICAL SAMPLING BERBASIS WEB STUDI KASUS : INSITUT TEKNOLOGI TELKOM PURWOKERTO - Diovianto Putra Rakhmadani; Faisal Dharma Adhinata; Ariq Cahya Wardhana (LPPM Universitas Abdurrab, 2021)
The classroom is the principal place in the implementation of teaching and learning activities. Classroom comfort indirectly affects the learning atmosphere and the comfort level of students in implementing teaching and learning activities. In its operational activities, classrooms have several supporting tools such as blackboards, projectors, air conditioners, chairs, and desks. These objects often experience problems such as minor damage, decreased function, to heavy damage. The existence of these obstacles can make teaching and learning activities less qualified in an academic classroom. Facilities and infrastructure to support quality teaching and learning activities require an inventory information system with quality control methods to ensure the classroom's quality of facilities is maintained. This research uses the Waterfall software development method and produces a web-based computerized system that can be used to monitor the quality of classroom facilities and follow-up. With this system, the quality of facilities and infrastructure in the classroom is maintained.